Access control policy management based on extended-XACML - LI Xiao-feng; FENG Deng-guo; XU Zheng (Tongxin xuebao)
Based on XACML core specification and XACML administrative policy draft,a decision of XACML policy management permission was reduced to a decision of delegation decision request.The delegation decision request schema was defined.It was described that the process of reducing a policy administration request to a delegation decision request and the decision process of delegation decision request.This method can be used to check if a policy administra-tion request is valid and thereby to implement access control policy management based on extended-XACML.